HUBUNGAN NAIK TURUN TANGGA DENGAN KEMEMPUAN BLOCK BOLA VOLI TERHADAP SISWA KELAS X MA DAAR ET-TAQWA PETIR KABUPATEN SERANG - Nana Hadi Permana; Ridwan Sudirman (Universitas Setia Budhi Rangkasbitung, 2021)
This research method is a quantitative method with a correlation approach. This sampling technique is called random sampling of the entire class. This technique is intended to make researchers more efficient because they do not require many objects. In this process, the researcher gives equal rights to each subject to get the opportunity to be a sample. Thus the sample of this study amounted to 30 students as respondents. The conclusions in this study are: The results of statistical analysis between there is a significant relationship between the method of going up and down stairs (X) and the ability to block volleyball, the value of t = 2.39, t table = 0.654 means that there is tolerance between the two variables. With the correlation table r = 0.45 is in the strong category. Thus, the alternative hypothesis of a significant relationship between the method of going up and down stairs (X) and the ability to block volleyball, then 2.39 > 0.654 the hypothesis Ha is accepted. It can be concluded that the hypothesis Ha stated: